Tratamento da hipertensão arterial com olmesartana medoxomila em escalonamento - Gomes, Marco Antônio Mota (2008)
BACKGROUND: The national and international guidelines emphasize the importance of the effective treatment of essenssial hypertension. Nevertheless, low levels of control are observed, as well as low attainment of the recommended goals, indicating that it is important to plan and implement better treatment strategies. OBJECTIVE: To evaluate the efficacy of a based treatment algorithm with olmesartan medoxomil. METHODS: This is an open, national, multicentric and prospective study of 144 patients with primary arterial hypertension, stages 1 and 2, naïve to treatment or after a 2-to-3 week washout period for those in whom treatment was ineffective. The use of olmesartan medoxomil was assessed in a treatment algorithm divided into 4 phases: (i) monotherapy (20 mg), (ii-iii) associated to à hydrochlorothiazide (20/12.5 mg and 40/25 mg) and (iv) addition of amlodipine besylate (40/25 mg + 5 mg). RESULTS: At the end of the phased-treatment, 86% of the study subjects attained the goal of BP < 130/85 mmHg. Maximum reductions in SAP and DAP were -44.4 mmHg and -20.0 mmHg, respectively. The rate of systolic responders (SAP > 20 mmHg) and of diastolic responders (DAP > 10 mmHg) was 87.5% and 92.4%, respectively. CONCLUSION: The study was based on a treatment regimen that was similar to the therapeutic approach in daily clinical practice and showed that the use of olmesartan medoxomil in monotherapy or in association with hydrochlorothiazide and amlodipine was effective in the attainment of the recommended goals for hypertension stage 1 and 2 hypertensive individuals.